Self-regulation for Managerial Effectiveness: The Role of Active Feedback Seeking - Ashford, Susan J.; Tsui, Anne S. (Academy of Management Journal, 1991)
This field study examined the feedback-seeking behavior of 387 managers as observed by their superiors, subordinates, and peers. Results suggest that managers' tendency to seek negative feedback increased the accuracy of their understanding about how these feedback sources evaluated their work. Seeking negative feedback further enhanced the three constituencies' opinions of the managers' overall effectiveness. Seeking positive feedback, in contrast, decreased constituents' opinions of the managers' effectiveness. Such results demonstrate the importance of both instrumental and impression-management concerns in the feedback-seeking process and support the proposition that active feedback seeking is a central part of a total process of self-regulation for managerial effectiveness.